Evaluation of the awareness of childhood cancers by generalpractitioners, family physicians and pediatricians - (:unkn) unknown (My University, 2020)
Objective: Although, childhood cancer was considered as a deadly disease in the past, now it is considered as a life-threateningchronic disease if diagnosed early. The present study evaluates how much the symptoms of childhood cancers are recognised by thephysicians in Istanbul, Turkey.Materials and Methods: The objective of the study and the questionnaire form was explained to participants and they were askedwhether they would like to take part in the study. The questionnaire composed of two sections: 1. Investigated the sociodemographiccharacteristics of the physicians and 2. Investigated the knowledge of the physicians on childhood cancers (leukaemia, solid tumour,common questions). The physicians were given 2 points for every correct answer; wrong answers and answers such as “I have no idea”were scored 0 points. Based on the correct answers given by all participants, the medians for every question group were calculated.The measure of success was 75 percentile, which was calculated for each question group considering these median values.Results: Examining the percentages of the correct answers to the questions, the best known were the leukaemia questions (74.6%)and the less known were the solid tumour questions (57.1%). The physicians younger than 33 years, which was the mean age, gavebetter answers to the leukaemia questions and the common questions. When the academic titles of participants were grouped aspediatricians and other physicians, the leukaemia, solid tumour, common group and total points showed statistically high significantdifferences.Conclusion: Our study has revealed the need of our country for training programs aimed at increasing the awareness of generalpractitioners working in primary health care institutions, as these institutions are the first reference centers for the pediatric patientpopulation. Childhood cancer awareness must be improved by implementing training programs which in turn will lead to earlydiagnosis and referral to an appropriate specialist.